1974
DOI: 10.1126/science.185.4147.269
|View full text |Cite
|
Sign up to set email alerts
|

Lectins: A Possible Basis for Specificity in the Rhizobium —Legume Root Nodule Symbiosis

Abstract: Soybean lectin labeled with fluorescein isothiocyanate combined specifically with all but 3 of 25 strains of the soybean-nodulating bacterium Rhizobium japonicum. The lectin did not bind to any of 23 other strains representative of rhizobia that do not nodulate soybeans. The evidence suggests that an interaction between legume lectins and Rhizobium cells may account for the specificity expressed between rhizobia and host plant in the initiation of the nitrogen-fixing symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
157
1
2

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(165 citation statements)
references
References 8 publications
5
157
1
2
Order By: Relevance
“…In a pioneering work, Bohlool and Schmidt (2) tested the ability of FITC3-labeled soybean seed lectin to bind to 25 strains of Rhizobium japonicum, the symbiotic species for soybean, and to 23 other strains representative of several Rhizobium species which do not nodulate soybean. They reported that the SBL bound to 22 to the 25 strains of the soybean symbiont, R. japonicum, and that the lectin did not bind to any of the 23 nonsymbiotic strains.…”
mentioning
confidence: 99%
“…In a pioneering work, Bohlool and Schmidt (2) tested the ability of FITC3-labeled soybean seed lectin to bind to 25 strains of Rhizobium japonicum, the symbiotic species for soybean, and to 23 other strains representative of several Rhizobium species which do not nodulate soybean. They reported that the SBL bound to 22 to the 25 strains of the soybean symbiont, R. japonicum, and that the lectin did not bind to any of the 23 nonsymbiotic strains.…”
mentioning
confidence: 99%
“…The first nodules were noted on day 3. The bulk of the nodules in the NRH zone emerged on day 5 (Fig. 4).…”
Section: Reactionmentioning
confidence: 99%
“…There is mounting evidence that lectins from certain legumes are bound by cells of Rhizobium strains that infect these plants (3,5,10), although other reports have been unable to support such findings (e.g. 16,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 "-'16) We also have reported the possible involvent of spore agglutinating factor in host plants in host-parasite specificity using Ceratocystis fimbriata Ell. and HaIst., black rot fungus.…”
mentioning
confidence: 94%